Multivariate characterisation of environmental conditions for reindeer husbandry in Sweden - Lundqvist, Henrik; Norell, Lennart; Danell, Öje (Rangifer, 2009)
Pastoralism using semi-domesticated reindeer (Rangifer t. tarandus) is a traditional livelihood in northern Fennoscandia. The area used for reindeer herding in Sweden covers as much as half of the country’s area. Variation in the productivity of reindeer husbandry is clearly affected by many biotic and abiotic factors. The aim of this investigation was to identify factor combinations which describe the spatial variation in conditions that plausibly determine productivity in reindeer herding. Initially, 37 variables representing geographical location, climate, weather episodes related to ice crust formation and insect harassment, topography, vegetation, forage abundance and qualities, and fragmentation of the ranges were derived, using prior ecological knowledge and spatially explicit data. The variables were mapped in a raster of 1958 squares of 100 km2 each, covering the entire Swedish reindeer herding area. Reductions of variables were performed with multivariate analyses in steps, ultimately retaining 15 variables. The first five principal components (PCs) of these variables explained 84% of the total variation. The first component, related to major western mountain/eastern lowland gradients, already accounts for 49% of the variation. The following components explained variation ranging from 10% to 5.4%, and revealed spatial patterns in summer versus winter forage, climatic conditions and ice crust formation, abundance of forests and winter forage, and northward slopes together with valuable forest areas, respectively. A tentative zone division of the Swedish reindeer herding area into seven zones was made, based upon cluster analysis and spatial distribution of component scores. Extending this approach and method seems useful also in the understanding and management of other natural resources and national parks, especially with an ongoing global climate change perspective.Abstract in Swedish / Sammandrag:Multivariat karakterisering av grundförutsättningar för renskötsel i Sverige. Den areal som nyttjas av renskötseln i Sverige täcker ungefär halva landets yta. Renens produktivitet varierar inom området beroende på många biotiska och abiotiska faktorer. Målet var att identifiera kombinationer av underliggande faktorer som kan orsaka den varierade produktiviteten inom renskötseln. Baserat på tidigare kunskap och spatiella data valdes 37 variabler som beskriver relevant variation i geografisk belägenhet, klimat, väderhändelser relaterade till skareförekomst och insektsstörningar, topografi, vegetation, betesmängd och -kvalitet, samt fragmentering av betesland. Värdena i dessa variabler beräknades för 1958 kvadrater à 100 km2, som tillsammans täckte hela renskötselområdet. Materialet analyserades med en stegvis principalkomponentanalys och klusteranalys, varvid antalet variabler reducerades till 15. De fem första principalkomponenterna, baserade på 15 variabler, förklarade tillsammans 84% av den samlade variationen, varav den första principalkomponenten ensam förklarade 49% och de efterföljande fyra komponenterna stod för vardera mellan 10 och 5,4%. Tolkningen av den första komponenten tyder på att den främst förklarade väntade öst-västliga gradienter i topografiska och klimatologiska förhållanden. De efterföljande principalkomponenterna förklarade den samlade variationen i sommar- kontra vinterbete, klimatförutsättningar och skareförekomst, skog och vinterbetesfördelning, resp. nordsluttningar i kombination med värdefull skogsmark, utöver de gradienter som isolerats i första komponenten. Baserat på den spatiella utbredningen av principalkomponentvärden föreslår vi en uppdelning av renskötselområdet i sju zoner med avseende på faktorer av betydelse för renskötseln. Denna ansats och metodik förefaller vara väl lämpad för förståelse och förvaltning av naturresurser och skyddsvärda områden generellt, speciellt i ett globalt föränderligt klimat.